A study on cognitive profile in parkinsons disease - Ragasivamalini, S.; Gobinathan, S.; Balambighai, V. (International Journal of Advances in Medicine, 2025)
Background: Parkinson’s disease (PD) is a neurodegenerative disorder characterized by α-synuclein accumulation, leading to motor and non-motor complications. Cognitive decline in PD ranges from mild cognitive impairment to Parkinson’s disease-related dementia. This study aimed to examine the cognitive profile and identify the subclinical range of cognitive impairments in patients with Parkinson’s disease. Methods: This cross-sectional study was conducted on 85 patients with Parkinson’s disease at Sree Balaji Medical College and Hospital, Chennai, between October 2022 and January 2025. Standardized neuropsychological tests, including the MMSE, ACE-R, MoCA and FAB, were used for cognitive assessment. Demographic and clinical data were collected through interviews and medical records and cognitive function was assessed at baseline. Results: Most patients were male, 66 (77.6%) and 23 (27.1%) patients were aged 71-75 years. Parkinson’s disease duration was <5 years in 38 (44.7%) patients. Hypertension and diabetes were present in 64 (75.3%) and 39 (45.9%) patients, respectively. The most common Hoehn and Yahr stage was 2.5 in 17 (20.0%) patients, followed by stage 1 in 15 (17.6%) and stage 3 in 13 (15.3%) patients. MMSE scores showed mild cognitive impairment in 45 (52.9%) patients, moderate in 27 (31.8%) and severe in 13 (15.3%). MoCA scores indicated severe impairment in 26 (30.6%) patients, moderate impairment in 23 (27.1%), mild impairment in 21 (24.7%) and normal cognition in 15 (17.6%). Conclusions: The demographic profile showed a predominance of older adults. Comorbidities such as hypertension and diabetes mellitus are common and complicate PD management.